The Quality of Financial Reporting through Increasing the Competence of Internal Accountants and Accrual Basis - Setiyawati, Hari; Iskandar, Diah; Basar, Yusuf S. (International Journal of Economics, Business and Management Studies, 2018)
This research was conducted against the background of a phenomenon that occurred based on the audit results of the Audit Board of the Republic of Indonesia, namely the poor quality of financial reporting, especially in the local government, provinces and cities / districts. The survey was conducted in the provincial / district government in West Java and Banten as many as 37 regional governments. The results showed that internal accountant competencies had a positive effect on the quality of financial reporting, especially in local governments. Likewise with the application of accrual based government accounting standards is also influential, and the direction of its influence is also positive.